PENGARUH GAYA KOMUNIKASI PIMPINAN TERHADAP KINERJA KARYAWAN BIDANG KOMPONEN TREATMEN DI PT. BINTANG INDOKARYA GEMILANG BREBES - Nuralim Nuralim; Yusuf Sapari; Muhammad Kamaluddin; Lisna Novita (JIKE: Jurnal Ilmu Komunikasi Efek, 2021)
The success of a leader in directing his subordinates to produce performance cannot be separated from the organizational communication climate conditions that encourage the achievement of such performance. The communication made by the leader to his employees will be a bridge for the leader to be able to provide improvements to the performance of the team he leads. This study aims to determine the effect of leadership communication style on employee performance in the Component Gtreatment sector at PT Bintang Indokarya Gemilang Brebes. This research uses an explanative quantitative method. The population in this study were 195 employees of PT Bintang Indokarya Gemilang Brebes in the Component Treatment Sector. The sampling technique used is purposive sampling and obtained a sample of 66 people. Data collection in this study used a questionnaire distributed using a google form link. The tests carried out are Normality Test and Linearity Test. The hypothesis test used is simple linear regression. The results in this study can be concluded: Leadership Communication Style positively affects Employee Performance. The amount of Communication Style influence on employee performance was 0.753(75.3%). And obtained adjusted R Squere results of 0.382 or 38.2% this shows that employee performance variables are influenced by the variable leadership communication style of 38.2% while the remaining 61.8% is influenced by other factors beyond those discussed in this study. Keywords: Communication, Leadership Communication Style, Employee Performance, TLI (Transformational Leadership Inventory).